The Representation of Optimism in Eleanor H. Porter's Pollyanna - Ula Nadia Muntaza; Dina Dyah Kusumayanti; Erna Cahyawati (Tamaddun Life, 2022)
This paper examines the representation of optimism during the American progressive era in the novel Pollyanna. The analysis focuses on discovering the discourse of optimism and the critical position of the author. The theory of representation by Stuart Hall and the discursive approach by Michel Foucault were used. The contextual background and the narrations in the novel are collaborated in the analysis process to find the discourse of optimism and the critical position of the author. The result of this research shows that this novel represents optimism through the glad game and the characters' personality alterations who always look at good sides on everything and make comparison of descending life events. The study also shows that as a writer, Porter positions herself as person who supports optimism as the response in the progressive era in America. Keywords: glad game, optimism, pollyanna, positive psychology.